2017
DOI: 10.1002/smll.201700264
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Nitrogen-Doped Graphene Quantum Dots and Ni3 S2 Nanosheets: A Synergistic Electrocatalyst with Highly Enhanced Activity for Overall Water Splitting

Abstract: A noble-metal-free electrocatalyst is fabricated via in situ formation of nanocomposite of nitrogen-doped graphene quantum dots (NGQDs) and Ni S nanosheets on the Ni foam (Ni S -NGQDs/NF). The resultant Ni S -NGQDs/NF can serve as an active, binder-free, and self-supported catalytic electrode for direct water splitting, which delivers a current density of 10 mA cm at an overpotential of 216 mV for oxygen evolution reaction and 218 mV for hydrogen evolution reaction in alkaline media. This bifunctional electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(48 citation statements)
references
References 55 publications
(85 reference statements)
0
44
0
Order By: Relevance
“…To further verify the aforementioned results, the EIS measurements on Co 9 S 8 @C were performed at η=0.47 V from 10 5 to 0.01 Hz with an AC voltage of 5 mV. As shown in Figure c and the inset, these semicircle‐like patterns can be fitted using an equivalent circuit . By calculating all the fitted data for the Nyquist plots, it is found that R ct and R s values increase in the following order: Co 9 S 8 @C‐2 (R ct =2.76 Ω; R s =7.26 Ω)<Co 9 S 8 @C‐10 (R ct =4.81 Ω; R s =7.55 Ω)<Co 9 S 8 @C‐20 (R ct =9.65 Ω; R s =8.39 Ω).…”
Section: Resultsmentioning
confidence: 73%
“…To further verify the aforementioned results, the EIS measurements on Co 9 S 8 @C were performed at η=0.47 V from 10 5 to 0.01 Hz with an AC voltage of 5 mV. As shown in Figure c and the inset, these semicircle‐like patterns can be fitted using an equivalent circuit . By calculating all the fitted data for the Nyquist plots, it is found that R ct and R s values increase in the following order: Co 9 S 8 @C‐2 (R ct =2.76 Ω; R s =7.26 Ω)<Co 9 S 8 @C‐10 (R ct =4.81 Ω; R s =7.55 Ω)<Co 9 S 8 @C‐20 (R ct =9.65 Ω; R s =8.39 Ω).…”
Section: Resultsmentioning
confidence: 73%
“…To minimize the energy loss between the electrode and active sites in which the reaction takes place, the electronic conductivity of the catalyst and the interface between catalyst and electrode should be optimized. To address this issue, several effective approaches, including utilization of metallic nonoxide catalysts, and combining catalysts with conductive supports, have recently been developed and will be discussed in this part.…”
Section: Optimization Strategies For Transition Metal Based Oer Catalmentioning
confidence: 99%
“…[92] and CoP [93] can boost the HER performance owning to CQDs could reduce the bandgap and enhance charge transfer.…”
Section: Electrocatalysismentioning
confidence: 99%